1997
DOI: 10.1073/pnas.94.17.9332
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of latent and productive HIV type-1 infection in tonsillar CD4 + T cells

Abstract: Correlates of virus load and characteristics of virus-producing cells in tonsillar tissue were investigated. Our results suggest that when less than 1:100 tonsillar CD4 ؉ T cells from individuals infected with HIV type-1 (HIV-1) contain replication competent provirus, the level of CD4 ؉ T cells in tonsils is comparable to that observed in uninfected individuals. Virus load at or above this level was associated with low CD4 cell numbers in tonsillar tissue. Only a few percent of all infected T cells in tonsilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…One infected cell produces between 100 and 1,000 virus particles per day (24,25), and only ϳ1 in 10,000 virus particles is infectious (26,27). It is therefore likely that an uninfected CD4…”
Section: Discussionmentioning
confidence: 99%
“…One infected cell produces between 100 and 1,000 virus particles per day (24,25), and only ϳ1 in 10,000 virus particles is infectious (26,27). It is therefore likely that an uninfected CD4…”
Section: Discussionmentioning
confidence: 99%
“…Studies using a large cohort of HIV-1 patients at various stages of disease showed that a significantly higher degree of apoptosis of T cells correlated with rapid progression of the disease (17). Apoptosis occurs primarily in uninfected bystander cells, mainly in CD4 ϩ T cells and CD8 ϩ T cells in tonsillar tissues (46) and T cells, B cells, and DC in the lymph nodes (33) in vivo. These apoptotic cells have been shown to exceed the numbers of productively infected cells, further suggesting the occurrence of bystander cell death (11).…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5 However, in lymphoid tissue, the frequency of CD4 1 T cells with replication-competent proviral DNA is less than 1% during the asymptomatic period 1,4,5 and less than 1 in 1000 CD4 1 T cells are actually involved in active virus replication. 5,6 The current assumption is that HIV-1 virions trapped in the follicular dendritic cell (FDC) network account for the major part of HIV-1 RNA found in lymphoid tissue in chronic HIV-1 infection. [1][2][3][6][7][8] However, it is debatable whether FDC-associated virions dominate over intracellular viruses in lymphoid tissue.…”
Section: Introductionmentioning
confidence: 98%
“…[15][16][17][18][19][20] Whereas a high baseline 21,22 and week 24 posttherapy plasma HIV-1 RNA level 23 is predictive of clinical progression, a substantial initial decline in plasma HIV-1 RNA after therapy is inversely correlated with the probability of rebound plasma viremia. 24 Although HIV-1 viral load in plasma and blood lymphocytes correlates with virus replication in lymphoid tissue, 5,[15][16][17] little is known about the predictive value of viral parameters in lymphoid tissue.…”
Section: Introductionmentioning
confidence: 99%